ANALISIS KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING PADA MATERI VIRUS KELAS X MA NW SUKAMULIA TAHUN PELAJARAN 2019/2020 - Nening Listari (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2020)
This study aims to find out how the creative thinking ability of Class X MA NW Sukamulia students by applying the problem solving learning model to virus material. This type of research is a quasi experiment with the design of Pretest Posttest Control Group Design. The population and sample of this study were all students of class X taken using the sample random sampling technique. Class X A as an experimental class and class X B as a control class. The research data were obtained from the pretest and posttest results of the experimental class and the control class. The results of data analysis obtained the average value of the analysis of creative thinking indicators 1. Smooth thinking average value of post test experimental class> control class (67.42> 59.09) 2. Think broadly of the experimental class> control class (61.69> 53.90) 3. Think original experimental class> control class (66.67> 43.94) 4. Thinking in detail the experimental class> control class (63.64> 46.97). Based on the results of the analysis of hypothesis testing with the Independent Sample t test, it shows that the posttest value of Tcount>Ttable or 3.020> 1.71714. This shows that by applying the problem solving learning model can improve students' creative thinking skills.